Physical Condition Profile of Handball Athletes - Muhammad Fahmi Hidayat; Dhias Fajar Widya Permana (Sriwijaya Journal of Sport)
This research is descriptive quantitative research that aims to find out and provide an overview of the physical condition possessed and can be a reference in an effort to improve the physical condition and achievements of athletes realized through training programs. The instruments used are Push-ups, Sit-ups, Shuttle Run, Speed (30m Sprint), Standing Broad Jump, Sit and Reach, and Endurance (Multistage Fitness Test). The subjects in this study were men's handball athletes of the Bantaeng Regency PORPROV exhibition in 2022 consisting of 14 athletes. Subject selection using total sampling technique. The results of the study as a whole show that the explosive power component is in the excellent category with a percentage of 71.4%. The components of arm muscle strength, abdominal muscle strength, agility, flexibility, and endurance are in the good category with percentages of 28.6% (arm muscle strength), 35.7% (abdominal muscle strength), 35.7% (agility), 14.3% (flexibility), and 42.9% (endurance), respectively. The speed component is in the category with a percentage of 28.6%. So, it can be concluded that there are 5 components of the dominant physical condition, namely strength, agility, explosiveness, flexibility, and endurance, and 1 component that still needs to be improved, namely speed.